PERSEPSI PETANI TERHADAP PROGRAM SL-PHT DALAM MENINGKATKAN PRODUKTIVITAS DAN PENDAPATAN USAHATANI KAKAO (Studi Kasus Petani Kakao di Desa Sukoharjo 1 Kecamatan Sukoharjo Kabupaten Pringsewu) - Rendi Robiyan; Tubagus Hasanuddin; Helvi Yanfika (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2014)
The objectives of this research are to find out level of cocoa farmers’ perception toward cocoa farming Integrated Pest Management Field School (SL-PHT) program in increaseing cocoa productivity and farm income and factors related to cocoa farmers’ perception toward SL-PHT program in increaseing cocoa productivity and farm income. This research was conducted in Sukoharjo 1 Village as one of villages where the cocoa SL-PHT program took place. This study was held in August until October 2013. Twenty-six farmers as respondents were selected by using a census method. Analysis methods used in this research are descriptive and Rank Spearman’s correlation. The results showed that the level of cocoa farmers’ perception toward SL-PHT program was in a good classification, and cocoa SL-PHT program was beneficial in increasing productivity, income, and pest disease control of cocoa plants, the level of farming experience, level of farming knowledge, and level of farmers’ social interaction had a correlation to the level of cocoa farmers’ perception toward SL-PHT program in increasing cocoa productivity and farm income.  Whereas, level of farmers’ living need fulfillment had no correlation to the level of cocoa farmers’ perception toward SL-PHT program. Keywords: cocoa, perception, productivity, SL-PHT, farmers